Physicochemical and antibacterial effect of Soy Protein Isolate/Gelatin electrospun nanofibres incorporated with Zataria multiflora and Cinnamon zeylanicum essential oils - Raeisi, Mojtaba; Mohammadi, Masoud Aman; Coban, Ozlem Emir; Ramezani, Soghra; Ghorbani, Marjan; Tabibiazar, Mahnaz; Noori, Seyyed Mohammad Ali (Springer, 2021)
Recently, combination of nanotechnology and active food packaging provided new horizon to extend the shelf life of food. This study aimed to fabricate natural nanofibrous film incorporated with essential oils using the nanospinning technique and examine its antimicrobial activity. Constituents of Zataria multiflora and Cinnamon zeylanicum essential oils (EOs) were investigated by Gas Chromatography-Mass Spectrometry and their antimicrobial properties were examined. Subsequently, electrospun Soy Protein Isolate (SPI)/Gelatin was embedded with Zataria multiflora and Cinnamon zeylanicum EOs. Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectrometry (FTIR), and Thermogravimetric analysis (TGA) were done to evaluate the properties of electrospun fibers. The antimicrobial activity of nanofibrous films was evaluated. SEM revealed that the addition of 30% gelatin neutralized SPI charge, representing a significant increase in the diameter of nanofibers by 314.08 nm. Furthermore, TGA showed stability for Soy/Gel nanofibers. The fabricated nanofibrous film exhibited exquisite antimicrobial activity against Gram-negative and Gram-positive pathogens. For example, SPI-gelatin nanofibrous film incorporated with 20% Z. multiflora reduced 100% of S. aureus, B. cereus, and L.monocytogenes. The reduction for E. coli and S. typhimurium were 70% and 63%, respectively. We suggest that incorporating EOs with nanofibrous films can be a promising method to extend the shelf life of food and can be used in production for active food packaging.
Keywords: Active food packaging; Essential oils; Electrospinning; Antimicrobial packaging; Food quality; Nanotechnology